2015
DOI: 10.1007/s12035-015-9323-y
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA Haplogroup A Decreases the Risk of Drug Addiction but Conversely Increases the Risk of HIV-1 Infection in Chinese Addicts

Abstract: Drug addiction is one of the most serious social problems in the world today and addicts are always at a high risk of acquiring HIV infection. Mitochondrial impairment has been reported in both drug addicts and in HIV patients undergoing treatment. In this study, we aimed to investigate whether mitochondrial DNA (mtDNA) haplogroup could affect the risk of drug addiction and HIV-1 infection in Chinese. We analyzed mtDNA sequence variations of 577 Chinese intravenous drug addicts (289 with HIV-1 infection and 28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 44 publications
(58 reference statements)
1
11
0
Order By: Relevance
“…In this respect it is worth noting that the mtDNA haplotypes from this study were determined for normal colon cells for patients. Moreover, in line with the international recommendations [28][29][30][31][32][33][34], the accuracy of all mitogenome sequences used here was confirmed with phylogenetic methods in previous reports [22][23][24][25][26]. The above -mentioned quality measures guarantee the authenticity of the genotyping and further association results presented in this study.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In this respect it is worth noting that the mtDNA haplotypes from this study were determined for normal colon cells for patients. Moreover, in line with the international recommendations [28][29][30][31][32][33][34], the accuracy of all mitogenome sequences used here was confirmed with phylogenetic methods in previous reports [22][23][24][25][26]. The above -mentioned quality measures guarantee the authenticity of the genotyping and further association results presented in this study.…”
Section: Discussionsupporting
confidence: 88%
“…On the other hand, frequencies of non-R haplogroups were low and the frequency difference of the R macrohaplogroup between cases and controls was not large enough to consider a strong association according to the international recommendations [28][29][30][31][32][33][34]. Furthermore, this potential association was lost after Bonferroni correction.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…40 One study has showed that in Han Chinese patients showed that haplogroup A may decrease the risk of drug addiction. 50 This study also showed that HeLa cells overexpressing 8794T had decreased levels of ROS production compared with those overexpressing 8794C. 50 Sex has an important impact on metabolism, and sex hormones affect mitochondrial metabolism.…”
Section: Discussionmentioning
confidence: 76%